Empathy: An Integral Model in Clinical Social Work. Issue 2 (8th April 2020) - Clark, Arthur J; Butler, Carrie M
Abstract: Empathy has held a vital and enduring standing in the theory and practice of clinical social work. Defining and conceptualizing empathy is a continuing challenge in social work and across the human services. A multitude of definitions of empathy exist in the therapeutic literature, creating confusion relating to research findings and treatment processes. Recent trends emphasize an overarching and expansive way of conceiving empathic understanding in the therapeutic relationship and informing treatment practice. Multiple perspectives of empathy facilitate a broad and wide-ranging engagement of the practitioner and the client in the therapeutic process. With significant implications for clinical social workers, an integral model capitalizes on the engagement of empathy from multiple ways of knowing: subjective, objective, and interpersonal. Numerous clinical examples illustrate applications of the tripartite model in social work practice. The integral empathy model is amenable to research and training across therapeutic contexts in social work and related fields.